Impact of Methimazole Treatment on Magnesium Concentration and Lymphocytes Activation in Adolescents with Graves’ Disease - Klatka, Maria (Humana Press Inc, 2013)
The aim of this research was to assess plasma magnesium (Mg) concentration, the frequencies of activated T CD4+ and T CD8+ lymphocytes and B lymphocytes in adolescents with hyperthyroidism due to Graves’ disease (GD), and to assess changes in the above-mentioned parameters during methimazole (MMI) treatment. The frequencies of activated T and B cells were measured by flow cytometry method and plasma Mg concentration was determined by spectrophotometry method in 60 adolescents at the time of GD diagnosis and after receiving the normalisation of the thyroid hormones levels. The control group consisted of 20 healthy volunteers. We observed lower plasma Mg concentration, and higher frequencies of activated T and B lymphocytes in the study group before the treatment in comparison with healthy controls, and with study group in MMI-induced euthyreosis (p < 0.01).Statistically significant negative correlations between the percentages of activated T CD3+, T CD4+, T CD8+ and B CD19+ lymphocytes, and plasma Mg concentration before the treatment were found (r < −0.335, p < 0.002). After the treatment no vital differences in plasma Mg concentration, and in percentages of activated cells between GD patients and controls were found, except CD8+CD25+ cells (p = 0.03). The present study demonstrates that both activated T and B cells might play an important role in the pathogenesis of GD, and activation is related to Mg plasma level. The use of MMI in treatment of hyperthyroidism due to GD leads to decrease the frequencies of activated lymphocytes and normalisation of Mg levels.